Actin cytoskeleton and membrane interactions: role in GPCR function and organization - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Proceedings of the Indian National Science Academy, 2019)
Cell signaling networks are generally initiated at the cell membrane and mediated by receptors such as the G proteincoupled receptors (GPCRs). Adjacent to the cell membrane lies a complex network of proteins - the actin cytoskeleton to which several structural and physiological roles have been attributed. An emerging role of the cytoskeleton is to modulate GPCR function and organization, either directly or indirectly. The GPCR-cytoskeleton cross-talk is a complex hierarchical process where each step has its own set of rules and combinations. Due to the inherent complexity involved at each step and the multiple spatio-temporal levels, a complete picture is yet to emerge. In this review article, we provide an overview of actin-membrane interactions and how they modulate GPCR function and organization.

Interplay between membrane curvature and cholesterol: role of palmitoylated caveolin-1 - Krishna, Anjali; Sengupta, Durba (Biophysical Journal, 2019)
Caveolin-1 (cav-1) is an important player in cell signaling and endocytosis that has been shown to colocalize with cholesterol-rich membrane domains. Experimental studies with varying cav-1 constructs have suggested that it can induce both cholesterol clustering and membrane curvature. Here, we probe the molecular origin of membrane curvature and cholesterol clustering by cav-1 by using coarse-grain molecular dynamics simulations. We have performed a series of simulations of a functionally important cav-1 construct, comprising the membrane-interacting domains and a C-terminal palmitoyl tail. Our results suggest that cav-1 is able to induce cholesterol clustering in the membrane leaflet to which it is bound as well as the opposing leaflet. A positive membrane curvature is observed upon cav-1 binding in cholesterol-containing bilayers. Interestingly, we observe an interplay between cholesterol clustering and membrane curvature such that cav-1 is able to induce higher membrane curvature in cholesterol-rich membranes. The role of the cav-1 palmitoyl tail is less clear and appears to increase the membrane contacts. Further, we address the importance of the secondary structure of cav-1 domains and show that it could play an important role in membrane curvature and cholesterol clustering. Our work is an important step toward a molecular picture of caveolae and vesicular endocytosis.

Sphingomyelin effects in caveolin-1 mediated membrane curvature published as part of the journal of physical chemistry virtual special issue ``computational and experimental advances in biomembranes'' - Krishna, Anjali; Prakash, Shikha; Sengupta, Durba (Journal of Physical Chemistry B, 2020)
The caveolin-1 (cav-1) protein is an integral component of caveolae and has been reported to colocalize with cholesterol and sphingomyelin-rich curved membrane domains. Here, we analyze the molecular interactions between cav-1 and sphingomyelin containing bilayers using a series of coarse-grain simulations, focusing on lipid clustering and membrane curvature. We considered a palmitoylated-cav-1 construct interacting with phospholipid/cholesterol membranes with asymmetrically distributed sphingomyelin, varying between 5 and 15% in total. We observe that cav-1 binds to the intracellular leaflet and induces a small positive curvature in the leaflet to which it is bound and an opposing negative curvature in the extracellular leaflet. Both cholesterol and sphingomyelin are observed to cluster in cav-1 bound membranes, mainly in the extracellular leaflet. Due to their negative spontaneous curvature, clustering of cholesterol and sphingomyelin facilitates membrane curvature such that the extent of either cholesterol or sphingomyelin clustering is dependent on the curvature induced. Our results suggest that cav-1 binding induces concentration-dependent curvature effects in sphingomyelin-rich membranes. Overall, our work is an important step in understanding the molecular basis of curvature and lipid clustering in cav1 bound cellular membranes.

Caveolin induced membrane curvature and lipid clustering: two sides of the same coin? - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Faraday Discussions, 2021)
Caveolin-1 (cav-1) is a multi-domain membrane protein that is a key player in cell signaling, endocytosis and mechanoprotection. It is the principle component of cholesterol-rich caveolar domains and has been reported to induce membrane curvature. The molecular mechanisms underlying the interactions of cav-1 with complex membranes, leading to modulation of membrane topology and the formation of cholesterol-rich domains, remain elusive. In this study, we aim to understand the effect of lipid composition by analyzing the interactions of cav-1 with complex membrane bilayers comprised of about sixty lipid types. We have performed a series of coarse-grain molecular dynamics simulations using the Martini force-field with a cav-1 protein construct (residue 82-136) that includes the membrane binding domains and a palmitoyl tail. We observe that cav-1 induces curvature in this complex membrane, though it is restricted to a nanometer length scale. Concurrently, we observe a clustering of cholesterol, sphingolipids and other lipid molecules leading to the formation of nanodomains. Direct microsecond timescale interactions are observed for specific lipids such as cholesterol, phosphatidylserine and phosphatidylethanolamine lipid types. The results indicate that there is an interplay between membrane topology and lipid species. Our work is a step toward understanding how lipid composition and organization regulate the formation of caveolae, in the context of endocytosis and cell signaling.

Caveolin mediated curvature and clustering: from simple to complex membrane - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Biophysical Journal, 2021)

Cofilin-membrane interactions: electrostatic effects in phosphoinositide lipid binding - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (ChemPhysChem, 2023)
The actin cytoskeleton interacts with the cell membrane primarily through the indirect interactions of actin-binding proteins such as cofilin-1. The molecular mechanisms underlying the specific interactions of cofilin-1 with membrane lipids are still unclear. Here, we performed coarse-grain molecular dynamics simulations of cofilin-1 with complex lipid bilayers to analyze the specificity of protein-lipid interactions. We observed the maximal interactions with phosphoinositide (PIP) lipids, especially PIP2 and PIP3 lipids. A good match was observed between the residues predicted to interact and previous experimental studies. The clustering of PIP lipids around the membrane bound protein leads to an overall lipid demixing and gives rise to persistent membrane curvature. Further, through a series of control simulations, we observe that both electrostatics and geometry are critical for specificity of lipid binding. Our current study is a step towards understanding the physico-chemical basis of cofilin-PIP lipid interactions.
Keywords: complex membrane; lipid clustering; Martini coarse-grain simulations; Molecular dynamics simulations; Protein-lipid interactions